Arrhythmias caused by mutations in SCN5A in children. (14th October 2021) - Polyakova, E; Shcherbakova, N
Abstract: : Pathogenic genetic variants of the sodium channel alpha-subunit gene (SCN5A) is the leading cause of familial bradyarrhythmias. These diseases often manifest with syncope, have family segregation, and needs antiarrhythmic devices implantation, even in children. However, phenotypically these mutations can manifest as sick sinus syndrome (SSS), atrial fibrillation (AF), Brugada syndrome, and long QT syndrome. There are no studies on the prevalence of SCN5A mutations in children with arrhythmias. The aim is to study phenotypic and electrocardiographic manifestations of SCN5A-mutations in children with bradyarrhythmias. Methods: We analyzed the data of 26 patients with bradyarrhythmias, who underwent genetic testing, from the database of the Russian Pediatric Arrhythmia Center. Seventeen were the probands, and nine - family members. The average age was 15.4±4.5 (from 2 to 17). Whole-exome sequencing was performed for 18 patients, cardiovascular panels for others. Results: Variants of the sodium channel gene were detected in 3 family cases of arrhythmias and one sporadic case. In total, variants in SCN5A gene were found in 9 patients out of 26 (35%). In the first family, two sisters aged 6 and 17 have two biallelic variants of unknown significance in SCN5A gene. Both girls periodically have a Brugada marker on their ECG. The sisters both had syncope before the implantation of defibrillators. The girls' parents and older sister are clinically healthy, but the father previously had syncope. In the second family, a boy with a binodal disease, syncope, and an implanted pacemaker has two biallelic likely pathogenic variants in SCN5A gene. The boy's sister inherited only the mother's of SCN5A variant, showed a normal ECG in the first year of life, but then developed bradycardia within one year, and then joined the AVB of the 1st degree. Both parents had no clinical manifestations and no complaints. The third family included a mother and daughter with SSS and the heterozygous missense variant of unknown significance in SCN5A gene. Both of them do not need pacemaker implantation. The 12-year-old girl with two heterozygous variants of unknown significance in SCN5A gene had SSS, AF and underwent pacemaker implantation. Conclusion: Genetic variants of SCN5A were detected in 35% of patients with bradyarrhythmias. Electrocardiographic manifestations of arrhythmias in our patients with SCN5A variants are diverse – SSS, Brugada syndrome, atrial fibrillation. Phenotypic variability in the manifestation of the SCN5A mutation requires a more thorough study of bradyarrhythmias' genetic causes in children. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Clinical Research Institute of Pediatrics named after acad. Y.E.Veltishev at the Pirogov Russian National Research Medical University, Moscow, Russia